Non‐decoupled morphological evolution of the fore‐ and hindlimb of sabretooth predators - Martín‐Serra, Alberto (J Anat, 2017)
Specialized organisms are useful for exploring the combined effects of selection of functional traits and developmental constraints on patterns of phenotypic integration. Sabretooth predators are one of the most interesting examples of specialization among mammals. Their hypertrophied, sabre‐shaped upper canines and their powerfully built forelimbs have been interpreted as adaptations to a highly specialized predatory behaviour. Given that the elongated and laterally compressed canines of sabretooths were more vulnerable to fracture than the shorter canines of conical‐tooth cats, it has been long hypothesized that the heavily muscled forelimbs of sabretooths were used for immobilizing prey before developing a quick and precise killing bite. However, the effect of this unique adaptation on the covariation between the fore‐ and the hindlimb has not been explored in a quantitative fashion. In this paper, we investigate if the specialization of sabretooth predators decoupled the morphological variation of their forelimb with respect to their hindlimb or, in contrast, both limbs vary in the same fashion as in conical‐tooth cats, which do not show such extreme adaptations in their forelimb. We use 3D geometric morphometrics and different morphological indices to compare the fore‐ and hindlimb of conical‐ and sabretooth predators. Our results indicate that the limb bones of sabretooth predators covary following the same trend of conical‐tooth cats. Therefore, we show that the predatory specialization of sabretooth predators did not result in a decoupling of the morphological evolution of their fore‐ and hindlimbs. The role of developmental constraints and natural selection on this coordinate variation between the fore‐ and the hindlimb is discussed in the light of this new evidence.